Reminiscenses of Manichaeism in Augustine"s City of God - Oort, Johannes van (HTS teologiese studies, 2016)
This article aims to analyse all the passages in Augustine’s City of God in which he either explicitly or implicitly makes mention of Manichaeism and its doctrines. It turns out that, even in his later years, Manichaean doctrines were at the forefront of Augustine’s mind, although essential elements of his own doctrines (for instance, evil being the privation of good) have a clearly anti-Manichaean background. A close reading of all those anti-Manichaean passages further discloses some fairly unique particulars, such as, for example, the Manichaeans’ use and interpretation of John 8:44 and 1 John 3:8.